Combining Risk and Responsibility Perspectives: First Steps - Brinkmann, Johannes (2013)
Business activity can be analyzed through a ‘risk awareness’ perspective and a ‘responsibility awareness’ perspective. However, risk and responsibility are actually interdependent. Risk-taking triggers responsibility issues and taking responsibility means risking being asked critical questions. This article suggests some first steps for combining these two perspectives conceptually. After several introductory illustrations showing how risk and responsibility issues are intertwined, the article looks separately each at risk and at responsibility. Then the argument that such perspectives could be usefully combined is elaborated further from a theoretical angle and from a practical angle, by looking at various ethical issues and by presenting paradigmatic examples of balancing or sharing risk and responsibility related to leadership, to ERM and to insurance.
Keywords: Leadership; responsibility ethics; Responsibility; Risk Management; Risk perception; Risk